Inovasi Strategis di Era Digital:Mengintegrasikanalat AI ke dalam Strategi Berbasis SWOT untuk Keunggulan Kompetitif: Bukti dari Café Majas Space and Resto, Kota Bandung - Amira Muthi Ghassani; Lanina Pratiwi; Panji Setia Meijaya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of artificial intelligence (AI) technology has encouraged culinary micro, small, and medium enterprises (MSMEs) to integrate AI utilization into SWOT-based competitive strategies to sustain competitive advantage. This study aims to analyze the effect of SWOT-Based Strategy, AI Tool Usage, and Innovation Orientation on Sustainable Competitive Advantage at Café Majas Space and Resto, both partially and simultaneously. The study employs a quantitative approach with an associative-causal design, involving 37 respondents selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The results show that AI Tool Usage and Innovation Orientation have a significant positive partial effect on Sustainable Competitive Advantage, while SWOT-Based Strategy shows no significant partial effect. However, simultaneous testing reveals that all combinations of independent variables, including those involving SWOT-Based Strategy, have a significant positive effect on Sustainable Competitive Advantage, with the overall model explaining 60.5% of the variance (Adjusted R² = 0.569). These findings affirm that sustainable competitive advantage among culinary MSMEs in the digital era requires the simultaneous integration of SWOT-based strategy, AI technology utilization, and organizational innovation orientation.